Photo-Catalytic Reduction of Carbon Dioxide Over Alumina Doped Titanium Dioxide Catalyst - Muhamad Daud, Azizul Rahman (2013)
Carbon dioxide (CO2) is a major source of greenhouse gas effect which causes the increasing in the Earth's temperature. The continuously increasing CO2 level into the atmosphere is one of the most serious problems with regard to the greenhouse effect. One of the remediation to overcome this problem by using Photo-reduction process with prepared catalysts assisted by UV light. In this process, CO2 was converted to methanol (CH3OH) as a main product. In this study, the influence of the parameters on the catalytic activity with and without visible light irradiation and also effect of percentage of Al2O3 loading on TiO2 were focused. The catalyst was prepared using sol-gel method. The percentage of Al2O3 loading on TiO2 were set in range of 1.50 wt.% - 5.0 wt. %. In photo-reduction process, highly industrial CO2 was first flowed through NaOH solution with presence of Al2O3-TiO2 catalyst in the reactor. The main product was analyzed using High Performance Liquid Chromatography (HPLC). The results show that for maximum loading of Al2O3 into TiO2 catayst, the performance of photocatalytic activity was enhanced due to the metals will act as electron traps, facilitating electron–hole separation and promote the interfacial electron transfer process. In photo-reduction process, the conversion of CO2 into methanol was more effective with UV light compared to the process without UV light. As a conclusion, with presence of higher percentage of Al2O3 on TiO2 and UV light, the reduction of CO2 can be done successfully.